2009
DOI: 10.1007/s10482-009-9334-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity and transferability of the tetracycline resistance gene tet(M), carried on Tn916-1545 family transposons, in enterococci from a total food chain

Abstract: In the present study, 20 enterococci belonging to the species Enterococcus faecalis (12 strains), Enterococcus faecium (4), Enterococcus durans (2), Enterococcus hirae (1) and Enterococcus mundtii (1) and originating from a total production chain of swine meat commodities were analysed to investigate the diversity of their tetracycline resistance gene tet(M). PCR-RFLP and sequence analysis showed that the tet(M) gene of most strains can be correlated with the Tn916 transposon. Conversely, tet(M) of six E. faec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 22 publications
2
37
0
2
Order By: Relevance
“…PCR tests for the tet(M) gene on transconjugant plasmids were also negative. This result was similar to that obtained by Huys et al (2004), where no (Huys et al, 2004;Rizzotti et al, 2009). Although in the present study the donor E. faecium S27 lacked the int gene it was still able to transfer the tet(M) gene.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…PCR tests for the tet(M) gene on transconjugant plasmids were also negative. This result was similar to that obtained by Huys et al (2004), where no (Huys et al, 2004;Rizzotti et al, 2009). Although in the present study the donor E. faecium S27 lacked the int gene it was still able to transfer the tet(M) gene.…”
Section: Discussionsupporting
confidence: 91%
“…While selected strains of Enterococcus are used in starter cultures for the fermentation of meat products, other strains can be found in various foods as contaminants. Therefore, the food chain is considered to be one of the main routes for transmission of antibiotic resistance among the human microbiota (Rizzotti et al, 2009). Antibiotic resistant enterococci are common in foods of animal origin (Aslam et al, 2012;Jahan et al, 2013;Sánchez Valenzuela et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The tet(M) gene is typically chromosomal located and it is usually carried by Tn916 or related conjugative transposon (Chopra and Roberts 2001;Roberts 2005). The association of the tet(M) gene with conjugative elements is a important factor for spreading of tetracycline resistance in enterococci, which corroborate with outlook that Enterococcus species are important sources of antibiotic resistance genes by horizontal gene transfer in potentially pathogenic bacteria occurring also in the food chain (Rizzotti et al 2009). The transferability of the tetracycline resistance gene tet(M) from food Lactobacillus plantarum to Enterococcus faecalis was evaluated by Jacobsen et al(2007).…”
Section: Frequency Of Tet(m) and Tet(l) Genesmentioning
confidence: 55%
“…They found that under in vitro conditions the isolates from faeces more readily transferred the resistance to enterococci of human origin. Jasni et al [49] [52]. Transfer of tetracycline and erythromycin resistances from a human E. faecalis isolate was also demonstrated in a sausage fermentation model, even without antibiotic pressure and as early as within two days of fermentation [53].…”
Section: Transmission Of Tetracycline and Mls Resistancementioning
confidence: 96%